Heterogeneity of biologically active deadenylated protamine mRNA components isolated from rainbow trout testes. - Gedamu, L (1979)
Poly(A)+ protamine mRNA's were isolated from rainbow trout testes and deadenylated by treatment with calf thymus RNase H. Four subcomponents of deadenylated PmRNA (PmRNA1-4) were purified by electrophoresis on a 6% polyacrylamide gel in 8 M urea. Translation of each PmRNA subcomponent in the wheat germ S-30 cell-free system showed that all subcomponents are biologically active but each codes for two or more protamine polypeptides suggesting molecular heterogeneity. However, the deadenylated mRNA's can be categorized into two groups based on the spectrum of protamines whose synthesis they stimulate.